Islamic profit and loss sharing contracting versus regular equity in entrepreneurial finance: Risk sharing and managerial incentives - Abdulali Hadizada; Peter Nippel (The Journal of Entrepreneurial Finance (JEF), 2022)
An entrepreneur shares business risk with the investors providing capital for her firm. Risk sharing is per se beneficial, but also results in an agency problem from diminished incentives for the entrepreneur. This classical trade-off depends on the financial contracting between the entrepreneur and the financier. As an alternative to debt or equity, we consider musharaka financing, an Islamic profit and loss sharing contract. First, we show that debt is inferior to equity or musharaka even though debt financing ensures first best efforts in our model. Whether financing with equity or by use of musharaka results in higher utility for the entrepreneur depends on how the firm's risks are related and on the structure of the costs the entrepreneur has to bear when spending effort.
Keywords: D25; D81; D82; G32; L26; 650; Entrepreneurial finance; Islamic finance; Equity; Musharaka; Partnership; Profit and loss sharing; Risk sharing; Managerial incentives